HEALTH PROFILE OF THE ELDERLY ATTENDED AT FAMILY HEALTH BASIC UNITS (UBSF) IN ITUIUTABA, MINAS GERAIS - Melo, Janyne Vilarinho; Santos, Ana Lúcia de Medeiros; Faria, Lina Rodrigues de; Alves, Waneska Alexandra; Rezende, Alexandre Azenha Alves de; Calábria, Luciana Karen (Journal of Health Care, 2017)
Introduction: The aging process is characterized by biological changes that occur throughout life. These changes can cause diseases or organic dysfunctions, in which Chronic Non-communicable Diseases (DCNT) stand out. Objective: Considering the importance of DCNT, the study identified the socioeconomic and demographic profiles of the elderly assisted at Family Health Basic Units (UBSF) in the municipality of Ituiutaba/MG. Material and methods: A descriptive cross-sectional study was carried out on 149 elderly people assisted in 11 UBSF, who were interviewed through a semi-structured questionnaire. Results: Their mean age was 70 years old, most of them were of the female gender, literate and with up to four years of study. Approximately 90% of the elderly reported the use of allopathic drugs, 47% used herbal medicines and 19.5% used herbal medicines. Only 14.7% of the elderlies reported the concomitant use of these three treatment modalities. Most of the interviewees used 2 to 4 allopathic medications (51.7%). Regarding the self-reported diseases, the most prevalent diseases were those from the circulatory system (75.8%), especially hypertension (72.5%), as well as musculoskeletal system diseases (41.6%) and diabetes mellitus (39.9%). Conclusion: According to the data obtained, it was possible to perform a diagnosis of the elderly assisted at the UBSF of Ituiutaba/MG. These data are essential for the implementation of public, social and educational policies directed to this population, in order to meet the socio-economic and behavioral needs, aiming to promote a healthy and active aging.
Keywords: Aging; chronic diseases; drug utilization; epidemiology